Pembuatan Alat Pemotong, Pencampur dan Pengaduk Pakan Ternak Sapi dengan Metode Logika Fuzzy untuk Meningkatkan Efisiensi Pakan Ternak - Budhi Bakhtiar -; Roza Susanti -; Hedrick - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
The growth of cattle majorly affected by the type of fodder and its digestion system. To gain the healthy growth, cattle fed green grass and additional concentrate in form of mixed agricultural wastes such as rice straw, corn straw, etc and tofu residues in cattle fodder. Since cattle have no upper incisor, (insisivus), it use combination of its molar and its tongue to cut the grass or rice straw or corn straw, as the result more fodder like fresh grass, rice straws or corn scraws are wasted. If the wasted re-use by giving it back to cattle, it will not eat it, so it will cause inefficiency in feeding livestock. In order to solve that problem a chopping and mixing tool is needed, by using fuzzy method to control a dc motor constant speed to chopping grass, rice straws and corn straws, and then mixing with additional concentrate such as tofu wasted. Rice straws, corn straws and fresh grass are chopped in chopping section and mixed with tofu residues in the mixing section. When all the food material mixed and stired, the weight will be measures using a current sensor ACS712-20A. This sensor is used to measure the motor load. Furtheremore, if the more food materials place into this device, so, the faster the dc motor will rotate. When this device loaded 3000gr, the current measure is 4.53 ampere. The load position is not smooth will result the reading of the sensor always fluctuated. As the result, the fuzzy method applied will be optimal when the current is 4.22 ampere and the PWM fuzzy is higher than 252-mark is legible